IMPLEMENTASI PROGRAM PARKIR ELEKTRONIK DALAM MENINGKATKAN PENDAPATAN ASLI DAERAH (PAD) DI KABUPATEN TABANAN (STUDI KASUS DI KECAMATAN TABANAN) - Kristanti, Leony Jaya; Supriliyani, Ni Wayan; Dwi Wismayanti, Kadek Wiwin (CITIZEN CHARTER, 2021)
The electronic parking program is an innovation program in the field of road traffic and transportation that aims to maximize local revenue obtained from parking fees. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of the research were analyzed using three aspects according to Charles O. Jones, namely organization, interpretation, and application / application. Based on the results of the analysis, it shows that the electronic parking program in Tabanan District is still not running optimally, because there are still problems in several aspects such as a lack of competent human resources related to parking coordinators, no systematic schedule for parking attendants, lack of socialization to the community, not yet. there is a special target for electronic parking, and constraints on the budget in renewing and maintaining infrastructure. Keywords: Policy Implementation, Electronic Parking Program, Tabanan District